An Enzyme‐Mimicking Single‐Atom Catalyst as an Efficient Multiple Reactive Oxygen and Nitrogen Species Scavenger for Sepsis Management. Issue 13 (12th February 2020) - Cao, Fangfang; Zhang, Lu; You, Yawen; Zheng, Lirong; Ren, Jinsong; Qu, Xiaogang
Abstract: Sepsis, characterized by immoderate production of multiple reactive oxygen and nitrogen species (RONS), causes high morbidity and mortality. Despite progress made with nanozymes, efficient antioxidant therapy to eliminate these RONS remains challenging, owing largely to the specificity and low activity of exploited nanozymes. Herein, an enzyme‐mimicking single‐atom catalyst, Co/PMCS, features atomically dispersed coordinatively unsaturated active Co‐porphyrin centers, which can rapidly obliterate multiple RONS to alleviate sepsis. Co/PMCS can eliminate O2 .− and H2 O2 by mimicking superoxide dismutase, catalase, and glutathione peroxidase, while removing . OH via the oxidative‐reduction cycle, with markedly higher activity than nanozymes. It can also scavenge . NO through formation of a nitrosyl–metal complex. Eventually, it can reduce proinflammatory cytokine levels, protect organs from damage, and confer a distinct survival advantage to the infected sepsis mice. Abstract : Better than nanozymes : By mimicking triple antioxidant enzymes, conducting an oxidative‐reduction cycle, and formation of a nitrosyl–metal complex, an enzyme‐mimicking single‐atom catalyst (SAzyme) can quickly obliterate multiple reactive oxygen and nitrogen species (RONS) and reduce proinflammatory cytokine levels to alleviate sepsis.